2022
DOI: 10.3390/ijms23169489
|View full text |Cite
|
Sign up to set email alerts
|

CDNF Interacts with ER Chaperones and Requires UPR Sensors to Promote Neuronal Survival

Abstract: Cerebral dopamine neurotrophic factor (CDNF) is a neurotrophic factor that has beneficial effects on dopamine neurons in both in vitro and in vivo models of Parkinson’s disease (PD). CDNF was recently tested in phase I-II clinical trials for the treatment of PD, but the mechanisms underlying its neuroprotective properties are still poorly understood, although studies have suggested its role in the regulation of endoplasmic reticulum (ER) homeostasis and the unfolded protein response (UPR). The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 89 publications
(186 reference statements)
0
18
0
Order By: Relevance
“…SBD, substrate binding domain. (B) MANF and CDNF are members of the ER-localized multiprotein complex of chaperones, as demonstrated in affinity-purification mass spectrometry experiments (20,145). (C) MANF regulates IRE1α signaling under ER stress.…”
Section: Cdnf and Manf Molecular Interactionsmentioning
confidence: 98%
See 3 more Smart Citations
“…SBD, substrate binding domain. (B) MANF and CDNF are members of the ER-localized multiprotein complex of chaperones, as demonstrated in affinity-purification mass spectrometry experiments (20,145). (C) MANF regulates IRE1α signaling under ER stress.…”
Section: Cdnf and Manf Molecular Interactionsmentioning
confidence: 98%
“…Unlike classical NTFs, survival-promoting effects of exogenous CDNF and MANF on naïve dopamine neurons and other types of naïve neurons seem to be very low or possibly even non-existent (12,20,145). When CDNF was added to the culture media, it did not promote the survival of naïve primary SCG neurons, motoneurons, or DRG neurons in vitro, differently from the respective control NTFs, i.e., nerve growth factor, ciliary neurotrophic factor, and GDNF (12).…”
Section: Neuroprotection Of Cdnf and Manf By Regulating Uprmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data on the effects of CDNF on ER stress markers support the hypothesis of direct regulation of UPR pathways by CDNF 22 , 33 . Moreover, recent data showed that CDNF interacts with the main ER chaperone Bip (as known as GRP78) 34 , is upregulated and secreted in response to experimental ER stress, and protects cells from ER stress-induced cell death both in vitro and in vivo 24 , 35 .…”
Section: Introductionmentioning
confidence: 99%